Halal-Based MSME Strengthening Strategy Model as a Driver of Community Economic Growth - Mochamad Sumpena (Universitas Muhammadiyah Surabaya, 2025)
The halal industry is currently becoming a rapidly growing phenomenon in society. This research aims to identify sales strategies in the halal industry that can encourage the improvement of the community's economy—the efforts to improve the economy through various sales methods. The research method used is qualitative, collecting primary and secondary data through interviews and literature studies relevant to the research topic. This research was conducted in Cibinong Village, Bogor City, with the primary informants being shop owners who run halal industry businesses. From the results of the research, three main strategy models were found to improve the economy, namely first, creating superior products with a short duration of offering; this strategy is effective in attracting consumer interest because products have advantages in terms of materials, design, and prices so that people tend to buy in large quantities. Second, applying selling prices based on multiple products is a powerful tactic to lure consumers to buy more Muslim clothes. Third, producing products in pairs is a special attraction during certain moments, such as holidays, when many families want to wear uniforms.